2006
DOI: 10.1159/000092775
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma Antigen Isoforms in Serum from Cervical Cancer Patients

Abstract: Squamous cell carcinoma antigen (SCCA) is a serological marker of squamous cell carcinomas (SCC). To study whether any of the SCCA isoforms would provide additional and more specific/sensitive clinical information than total SCCA, immunoassays specific for the different forms of SCCA (free SCCA2, total SCCA2, total SCCA1 and total SCCA) were developed. SCCA isoforms were determined before therapy and in follow-up samples from patients with cervical cancer and in serum samples from healthy females. Serum sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…Serum tumor markers are known to be useful tools for early detection of recurrence and in the follow-up of cancer patients, and in some cases they may also provide independent prognostic information [12]. Recent evidence revealed that expression levels of several cytokines and proteins reflect PASI scores and that those levels in serum may be useful as indicators of psoriasis severity (such as IFN-γ, IL-6, TNF-α, and IL-8) [13, 14], but these studies failed to obtain quantitatively correlative results [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum tumor markers are known to be useful tools for early detection of recurrence and in the follow-up of cancer patients, and in some cases they may also provide independent prognostic information [12]. Recent evidence revealed that expression levels of several cytokines and proteins reflect PASI scores and that those levels in serum may be useful as indicators of psoriasis severity (such as IFN-γ, IL-6, TNF-α, and IL-8) [13, 14], but these studies failed to obtain quantitatively correlative results [15].…”
Section: Discussionmentioning
confidence: 99%
“…Serum concentrations of SCCA in squamous cell carcinoma patients are correlated with the clinical stage and the degree of histological tumor differentiation [12]. Studies have found upregulated expression of SCCA in both squamous cell carcinoma and psoriasis lesions [26], while the biological role of SCCA in psoriasis remains obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Data published so far conclude that it is not clear whether A1, A2 or both should be measured in clinical assays [7] . The clinical information gained with the Abbott assay is clearly biased towards measurement of A1.…”
Section: Discussionmentioning
confidence: 99%
“…However, discordance between detection of elevated serum tumor markers and the diagnosis was reported, and the serum tumor markers may not be elevated despite the presence of recurrent disease. 23 Bolli et al 24 reviewed charts of 272 patients followed up for cervical cancer with 1053 samples evaluated. Of the 70 patients whose conditions were diagnosed with recurrence, 81% had elevated values.…”
Section: Tumor Markersmentioning
confidence: 99%